Multiple Level Effects of Imazethapyr on Leptodactylus latinasus (Anura) Adult Frogs - Pérez-Iglesias, J. M.; Fanali, L. Z. [UNESP]; Franco-Belussi, L. [UNESP]; Natale, G. S.; De oliveira, C. [UNESP]; Brodeur, J. C.; Larramendy, M. L. (Springer Nature, 2021)
Imazethapyr is an herbicide that is used in a variety of crops worldwide, including soybean and corn. The aim of the present study was to evaluate the biomarkers responses of adult Leptodactylus latinasus exposed to the formulation Pivot® H (10.59% imazethapyr) in the laboratory at concentrations and under conditions that simulate two potential field exposure scenarios: an immersion in field runoff (Scenario 1: 10 mg/L) and a direct exposure to the droplets emitted by spray noozles (Scenario 2: 1000 mg/L). In both scenarios, the experimental procedure involved completely immersing the frogs over a period of 15 s. Different endpoints were evaluated at several ecotoxicological levels 48 and 96 h after the herbicide exposure. These included individual (biometric indices and behavior alterations), histological (liver pigments and lesions), biochemical (catalase, glutathione system and cholinesterase activities) and genotoxic effects (micronuclei induction and nuclear abnormalities). Forty-eight hours after imazethapyr exposure, frogs submitted to Scenario 1 presented an inhibition of liver glutathione-S-transferase activity, whereas histological alterations and increased hepatic cholinesterase levels were observed in frogs exposed under Scenario 2. Ninety-six hours after exposure to the imazethapyr formulation, frogs from the Scenario 1 treatment presented a decrease in liver melanin and hemosiderin, increased hepatic catalase activity and micronuclei induction. For their part, frogs exposed to Scenario 2 presented a decrease in the hepatosomatic index, an increase in liver alterations, melanin reduction and micronuclei induction. The multivariate analysis enables correlations to be made between biomarkers of different organizational level in exposed anurans. Our result indicates that real exposure to imazethapyr formulations under field conditions may pose a risk to Leptodactylus latinasus populations living in the agroecosystems.